2018
DOI: 10.1055/s-0038-1667376
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Depressive State and Maternal Cognitive Function in Postpartum Women

Abstract: Postpartum depression is common and appears to predominantly affect maternal self-assessment of cognitive ability, rather than a true cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A cohort study was performed. Women delivering during the COVID-19 pandemic were compared to historic unexposed group delivering singletons at term, at the same medical center, before the COVID-19 pandemic (Mazor et al 2019 ). Each woman was recruited and participated at a single time point (fixed estimate of time).…”
Section: Methodsmentioning
confidence: 99%
“…A cohort study was performed. Women delivering during the COVID-19 pandemic were compared to historic unexposed group delivering singletons at term, at the same medical center, before the COVID-19 pandemic (Mazor et al 2019 ). Each woman was recruited and participated at a single time point (fixed estimate of time).…”
Section: Methodsmentioning
confidence: 99%
“…Although there are no studies on DM in pregnant women with pre-natal depression, there has been some research into pregnancy and post-natal cognitive performance and mood. Many studies have shown that there may be cognitive changes in perinatal depression patients (41)(42)(43)(44)(45)(46). A Portuguese study Abbreviations: DM, decision-making; IGT, Iowa Gambling Task; PSQI, Pittsburgh Sleep Quality Index; EPDS, Edinburgh Post-natal Depression Scale; OFC, orbitofrontal cortex; VMPFC, ventromedial PFC.…”
Section: Introductionmentioning
confidence: 99%